The Relationship Between Nurse Performance and Inpatient Satisfaction in Regional Hospitals, Madani Pekanbaru City - Altrivel Saputra; Kurniawaty Fitri; Dian Puspita Novrianti (West Science Interdisciplinary Studies, 2024)
This study aims to test the relationship between nurse performance and inpatient satisfaction at Madani Regional Hospital in Pekanbaru City. The population of this study was inpatients at the Madani Regional Hospital of Pekanbaru City. This study consisted of two variables, including Nurse Performance (X), and Patient Satisfaction (Y).  The samples in this study amounted to 120 samples using the Purposive Sampling method. The analysis method in this study uses Kendall's test or data processing using SPSS (Statistical Package of Social Science) version 25.0. Based on the results of the analysis shows that the Nurse's Performance in the range is quite good and Patient Satisfaction is in the range is quite good in general. The results of the hypothesis test stated that Nurse Performance has a strong relationship with Inpatient Satisfaction at Madani Regional Hospital in Pekanbaru City. This means that the higher the Nurse's Performance, the more Inpatient Satisfaction at the Madani Regional Hospital in Pekanbaru City.